2015
DOI: 10.4103/0971-6580.172272
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis as harbinger of phenytoin toxicity

Abstract: Psychosis with phenytoin use has earlier been reported only in the context of Vitamin B12 or folic acid deficiency. We report a rare case of phenytoin toxicity manifesting as psychosis in the absence of Vitamin deficiency. The importance of recognition of psychosis as a harbinger of phenytoin toxicity and implications for management are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Other factors that are associated with the onset of acute psychosis in various case reports include the concentrative or transcendental type of meditation,[ 193 ] COVID-19 vaccine,[ 194 ] drugs like iohexol,[ 175 ] phenytoin,[ 176 177 ] levetiracetam,[ 178 ] disulfiram,[ 179 180 181 ] a combination of baclofen and disulfiram,[ 182 ] armodafinil,[ 183 ] ciprofloxacin,[ 184 ] bupropion,[ 185 ] mephentermine,[ 186 ] antitubercular drugs[ 187 ] like cycloserine,[ 188 189 ] ethambutol,[ 190 ] a combination of interferon alpha2B and ribavarin,[ 191 ] and dapsone. [ 192 ]…”
Section: Resultsmentioning
confidence: 99%
“…Other factors that are associated with the onset of acute psychosis in various case reports include the concentrative or transcendental type of meditation,[ 193 ] COVID-19 vaccine,[ 194 ] drugs like iohexol,[ 175 ] phenytoin,[ 176 177 ] levetiracetam,[ 178 ] disulfiram,[ 179 180 181 ] a combination of baclofen and disulfiram,[ 182 ] armodafinil,[ 183 ] ciprofloxacin,[ 184 ] bupropion,[ 185 ] mephentermine,[ 186 ] antitubercular drugs[ 187 ] like cycloserine,[ 188 189 ] ethambutol,[ 190 ] a combination of interferon alpha2B and ribavarin,[ 191 ] and dapsone. [ 192 ]…”
Section: Resultsmentioning
confidence: 99%
“…Gatzonis et al [8] reported the case of acute psychosis developing in a case of trigeminal neuralgia, which improved after stopping phenytoin, although serum levels were again normal. Borasi et al [9] are the only ones who report a chronic epileptic with a history of 15 years of phenytoin intake, presenting with acute psychosis and raised serum levels of the same, who improved after stopping phenytoin. Our case is the only one where a short history of the recommended dosage of phenytoin intake is associated with acute psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is a higher risk of psychosis in patients with epilepsy up to 6-12 times greater than the general population. The literature also shows cases of psychosis following the use of anti-epileptic drugs (AEDs) such as phenytoin and levetiracetam in epileptic patients [ 1 - 2 ]. Not only can each AED cause psychosis, but a mixed-methods study by Chen Z et al, (2016) revealed that the concurrent use of levetiracetam with another AED poses a serious risk of developing an anti-epileptic-induced psychosis in patients with epilepsy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%